The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/aob/mcw091
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling roots of lianas: a case study in Sapindaceae

Abstract: Background and Aims Roots are key in the evolution of plants, being in charge of critical functions, such as water and nutrient uptake and anchorage of the plant body. Stems of lianescent Sapindaceae conform to the anatomical patterns typical of climbing plants, having cambial variants in their stems and vessel dimorphism in their wood. The roots of these lianas, however, are largely unexplored, so we do not know whether the plant habit has as strong an impact on their anatomy as on the anatomy of their stems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 57 publications
(76 reference statements)
3
23
0
1
Order By: Relevance
“…This will result in the activity of tree roots literally being pushed to deeper soil layers where Ψ soil values are still less negative due to the presence of non-exhausted water reserves, which were replenished during the wet season. The ability of lianas to remain active in upper soil layers and to efficiently exploit the small rainfall input (see Figure S1 available as Supplementary Data at Tree Physiology Online) can potentially be attributed to the following reasons: (i) lianas are able to actively lower their osmotic potential to ensure the maintenance of a functional water potential gradient within the liana ( De Guzman et al 2016 , Maréchaux et al 2017 ); and (ii) lianas may be able to form hydraulic bridges by-passing embolized large vessels and ensuring an intact water column by their ability to anatomically adapt bimodal distribution of vessel diameter (i.e., vessel dimorphism) ( Bastos et al 2016 ). The strategy of maintaining an active upper root system might be very beneficial for lianas as this allows them to have a competitive advantage not only for water, but also a strong advantage for accessing nutrients in the upper soil layers, which may account for the dry season growth advantage of lianas as previously noted ( Schnitzer 2005 , Cai et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…This will result in the activity of tree roots literally being pushed to deeper soil layers where Ψ soil values are still less negative due to the presence of non-exhausted water reserves, which were replenished during the wet season. The ability of lianas to remain active in upper soil layers and to efficiently exploit the small rainfall input (see Figure S1 available as Supplementary Data at Tree Physiology Online) can potentially be attributed to the following reasons: (i) lianas are able to actively lower their osmotic potential to ensure the maintenance of a functional water potential gradient within the liana ( De Guzman et al 2016 , Maréchaux et al 2017 ); and (ii) lianas may be able to form hydraulic bridges by-passing embolized large vessels and ensuring an intact water column by their ability to anatomically adapt bimodal distribution of vessel diameter (i.e., vessel dimorphism) ( Bastos et al 2016 ). The strategy of maintaining an active upper root system might be very beneficial for lianas as this allows them to have a competitive advantage not only for water, but also a strong advantage for accessing nutrients in the upper soil layers, which may account for the dry season growth advantage of lianas as previously noted ( Schnitzer 2005 , Cai et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of peripheral vascular strands (Figs 2A–2C and 4A & 4B ), vessel dimorphism (Figs 2F & 2I and 4B–4D ), wide vessels solitary or in tangential multiples of 2–3 ( Fig 2F and 4C ), narrow vessels in long radial multiples of 2–21 (Figs 2F and 4C & 4D ), alternate intervessel pits with slit-like coalescent apertures (Figs 2G and 2H and 4E ), heterocellular rays, prismatic crystals in axial parenchyma (Figs 3D and 4F ), and dark content (possibly phenolic compounds) in primary vascular parenchyma and ray parenchyma ( Fig 2D and 2E ) support the inclusion of Ampelorhiza in Paullinieae [ 13 , 16 , 18 , 64 , 66 , 92 , 93 , 94 ]. Two wood anatomical characters typical of extant Paullinieae were not observed in the fossils: 1) alternating bands of thin and thick-walled regions in the wood which may either be axial parenchyma alternating with ordinary fibers (e.g., Serjania spp.)…”
Section: Discussionmentioning
confidence: 76%
“…Although cambial variants are often associated with the climbing habit, the presence of peripheral vascular strands is not sufficient to identify the fossils as stems or roots. Bastos et al [ 16 , 66 ] demonstrated that cambial variants can be found in both organs. In stems of Paullinieae, the pith is conspicuously angular (e.g., triangular, pentangular) in transverse section with primary vascular bundles at the corners [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations